Hyperinflation argentine de 1989 : une interprétation post-keynésienne - Jonathan Marie (Revue de la Régulation)
The purpose of the article is twofold. Firstly, it aims at proposing a Post-Keynesian interpretation of hyperinflation. The theoretical building includes elements suggested by Post-Keynesians as well as by structuralists. The accent is put on the role played by a foreign currency in domestic comportments during high inflation periods. Besides, a definition of hyperinflation is suggested: hyperinflation could be seen as a substitution by a foreign currency of a domestic currency. This substitution, violent in its final step, is built gradually. Hyperinflation is caused by a violent distributive conflict which generates a strong inflation, by indexation, by an external indebtedness denominated in a foreign currency and by self-fulfilling prophecies. Secondly, this theoretical framework is confronted to economic facts observed in Argentina from the 1970’s to the 1989 hyper-inflationist spurt. The historical political economy analysis allows the spotting of the following sequence: the distributive conflict is highly violent, reshaped several times from the 1970’s onwards. It provokes the development of institutional arrangements (indexation), while the dollar becomes more and more important within the economy. This phenomenon is encouraged by the implementation of an original exchange rate regime at the end of the 1970’s, in a context of liberalization of the economy. The impossibility to stabilize the exchange rate during the 1980’s in a context of external indebtedness makes possible the arising of hyperinflation. It is finally activated by speculation on the exchange rate level and a run on the foreign reserves.